Evaluations of temperature measurements in powder-based electron beam additive manufacturing by near-infrared thermography. (1st January 2014) - Price, Steven; Cooper, Kenneth; Chou, Kevin
Powder-based electron beam additive manufacturing (EBAM) has received an increased attention from different industries for various applications. Process metrology such as part temperature measurements is essential to process model validations as well as process monitoring. However, temperature measurements in EBAM are challenging because of high temperature ranges, extreme gradients and fast transient response, etc. In this study, temperature measurements during the EBAM process were attempted using a near-infrared (NIR) thermal camera. The thermal camera was able to capture the pre-heating, contour melting, and hatch melting events. The best obtained spatial resolution is around 12 μm. Moreover, temperature data were processes and analysed to illustrate the process phenomenon, analogy to a moving heat source event. Moreover, from the extracted temperature profiles, a melting range can be identified and utilised for melt pool geometry estimates. It is shown that a typical melt pool in hatch melting from this test is about 1.91 mm long and 0.63 mm wide.